Impact of Financial Crisis on Non-Traditional Income: Islamic Banks vis a vis Conventional Banks - Alfarisi, Mohamad Fany (Journal of Islamic Finance, 2015)
The present study aims to investigate the existing of shock due to the subprime financial crisis (2008) to the commercial banks performance in ASEAN-5 countries (Indonesia, Malaysia, Singapore, Thailand, and Philippine) particularly on the non-traditional activities aspect. Commercial banks in the present study are classified into Islamic and conventional banks. The data of 136 commercial banks in ASEAN-5 countries during the period of 2004-2012 from have been collected from the Bankscope database. The composition of sample based on type of bank is twenty samples are categorised as Islamic banks and the remaining 116 samples are under the category of conventional banks. We manage to run panel data regression using three estimation methods namely pooled-OLS, fixed effects and random effects methods. Based on the Breusch and Pagan Lagrangian Multiplier (LM) and Hausman tests, the random effects method is preferred. Islamic banks earn relatively lower non-traditional income compared to conventional banks. During the 2008 financial crisis commercial banks earn relatively lower non-interest income. Additionally, we find no evidence than Islamic and conventional banks non-traditional incomes are significantly different during the 2008 global financial crisis.